Psychological and Contextual Factors in English Vocabulary Learning - He, Yuwei; Wang, Rong; Wang, Ting; Duan, Suyi (Journal of Theory and Practice in Education and Innovation, 2025)
This paper synthesizes research on English vocabulary learning, emphasizing the roles of psychological factors (e.g., attention stability, motivation), contextual influences (e.g., multimedia, gamification), and technological interventions (e.g., digital tools, AI). Findings highlight the interplay of learning pace, cognitive engagement, and strategic behaviors in optimizing vocabulary acquisition. Future directions suggest integrating neurocognitive methods and adaptive technologies to personalize learning. The study underscores the need for multifaceted approaches to enhance vocabulary outcomes across diverse learners.